Downregulation of Cyp7a1 by Cholic Acid and Chenodeoxycholic Acid in Cyp27a1/ApoE Double Knockout Mice: Differential Cardiovascular Outcome - Zurkinden, Line; Sviridov, Dmitri; Vogt, Bruno; Escher, Genevieve (Frontiers in Endocrinology, 2020)
Sterol 27-hydroxylase (CYP27A1) is a key enzyme in bile acids (BAs) biosynthesis and a regulator of cholesterol metabolism. Cyp27a1/Apolipoprotein E double knockout (DKO) mice fed with western diet (WD) are protected from atherosclerosis via up-regulation of hepatic Cyp7a1 and Cyp3a11. Since feeding BAs ameliorates metabolic changes in Cyp27a1 KO mice, we tested BAs feeding on the development of atherosclerosis in DKO mice. DKO mice were fed for 8 weeks with WD containing 0.1% cholic acid (CA) (WD-CA) or chenodeoxycholic acid (CDCA) (WD-CDCA). Atherosclerotic lesions, plasma lipoprotein composition and functionality, hepatic lipid content, BAs amount and composition, expression of genes involved in lipid metabolism and BA signaling in liver and intestine as well as intestinal cholesterol absorption were assessed. Hepatic Cyp7a1 and Cyp3a11 expression were reduced by 60% after feeding with both WD-CA and WD-CDCA. After feeding with WD-CA we observed a 40-fold increase in the abundance of atherosclerotic lesions in the aortic valve, doubling of the levels of plasma total and low density lipoprotein cholesterol and halving of the level of high density lipoprotein cholesterol. Furthermore, in these mice plasma cholesterol efflux capacity decreased by 30%, hepatic BA content increased 10-fold, intestinal cholesterol absorption increased 6-fold. No such changes were observed in mice fed with WD-CDCA. Despite similar reduction on Cyp7a1 and Cyp3a11 hepatic expression, CA and CDCA have a drastically different impact on development of atherosclerosis, plasma and hepatic lipids, BAs composition and intestinal absorption. Reduced cholesterol absorption contributes largely to athero-protection in DKO mice.